2023
DOI: 10.3171/2023.3.focus2349
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a biparietal narrowing metric to improve the ability of machine learning models to detect sagittal craniosynostosis with 2D photographs

Abstract: OBJECTIVE Sagittal craniosynostosis is the most common form of craniosynostosis and typically results in scaphocephaly, which is characterized by biparietal narrowing, compensatory frontal bossing, and an occipital prominence. The cephalic index (CI) is a simple metric for quantifying the degree of cranial narrowing and is often used to diagnose sagittal craniosynostosis. However, patients with variant forms of sagittal craniosynostosis may present with a "normal" CI, depending on the part of the suture that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The impact of accurate input data was clearly illustrated by You et al, who found models with input data from senior surgeons to be more accurate than those from junior surgeons [13]. Second, a large set of training data verified by multiple surgeons is needed to ensure reliability which is a very time-consuming endeavour [7][8][9][10][11][12][13][14]. Several different craniometrics to classify craniosynostosis have been proposed in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The impact of accurate input data was clearly illustrated by You et al, who found models with input data from senior surgeons to be more accurate than those from junior surgeons [13]. Second, a large set of training data verified by multiple surgeons is needed to ensure reliability which is a very time-consuming endeavour [7][8][9][10][11][12][13][14]. Several different craniometrics to classify craniosynostosis have been proposed in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…When using their ML model of support vector regression, they were able to identify brachycephaly and plagiocephaly with 86.7% accuracy [ 8 ]. Likewise, Anderson et al demonstrated the use of 2D photographs to measure the posterior arc angle and the cephalic index [ 9 ]. These have been found to accurately classify sagittal craniosynostosis and have the potential to be incorporated into ML models [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations